Behavioral factor analysis of accuracy in using diarrhea medicines at Arjuno Health Center, Malang City with the Health Belief Model (HBM) approach - Laras Hadyaning Tias; Liza Pristianty; Ika Ratna Hidayati (Universitas Muhammadiyah Malang, 2020)
Diarrhea is a bowel movement that can occur in adults and children, with a frequency of three or more times a day, accompanied by stool to liquid changes, with mucus and blood. The Health Belief Model is a theory used to help identify factors that influence individual health behavior. This study aims to analyze patient behavior factors that influence the accuracy in using diarrhea medication at Arjuno Health Center Malang City, according to the HBM approach. This study used a cross-sectional method with the sampling technique used, namely a non-probability sample with an accidental method. This study uses an approach to the theory of the Health Belief Model (HBM). The research instrument used was a valid and reliable questionnaire. There are two variables used, namely the independent variable (the factors of the Health Belief Model theory) with five constructs, namely Perceived susceptibility, perceived severity, perceived barrier, perceived benefits, self-efficacy. Furthermore, the dependent variable with one indicator is the accuracy of using diarrhea medication. The number of samples used was 80 respondents. The T-test with a significance value for each HBM component is 0.000 < p-value (alpha = 0.05), which means an influence between each HBM component and the accuracy of drug use in patients with diarrhea. F test with a significant value for all HBM components 0.000 < p-value (alpha = 0.05), which means that there is an effect of all HBM components on drug use accuracy in patients with diarrhea.